BIOLOGICAL SYNTHESIS OF KERATIN NANOPARTICLES FROM DOVE FEATHER (COLUMBA LIVIA) AND ITS APPLICATIONS - NANTHAVANAN P; KANDASAMY ARUNGANDHI; SUNMATHI D; NIRANJANA J (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The aim of the present study was to synthesize keratin nanoparticles from dove feathers. Methods: Crude keratin was extracted by chemical method. The protein content was estimated by Lowry’s method and it was found to be 0.18 mg/ml. The keratin nanoparticles were obtained using glutaraldehyde as cross-linking agent. Results: A single peak maximum at 270 nm corresponds to the surface plasmon resonance of keratin nanoparticles was observed in the ultraviolet-visible spectrum. The size of keratin nanoparticles was 78 nm. The crystalline size of keratin nanoparticles was 79.6 nm and it was obtained by X-ray diffraction. The antibacterial activity of crude keratin and keratin nanoparticles was determined which revealed that keratin nanoparticles showed higher zone of inhibition than crude keratin protein against Staphylococcus aureus and Salmonella typhi. Keratin nanoparticles showed higher antioxidant activity than crude keratin. Conclusion: Biological synthesis of nanoparticles has many advantages such as ecofriendly and low cost and can be synthesized in large scale. The keratin nanoparticles can be applied in wound dressing, biosorbent, and cosmetics.